Resources, Potentials and Academic Achievements of Students. Part 2. From Differentiation to Integration of Resources, Potentials and Academic Achievements of Students - L. Ya. Dorfman; A. Yu. Kalugin (Russian State Vocational Pedagogical University, 2020)
Introduction. In Part 1, an analytical review of diverse studies into resources and potentials as prerequisites for academic success of university students was conducted. These categories were defined in terms of their differentiation. However, the opposite trend - their systemic integration - remains inadequately investigated.The aims of the present publication are the following: to reveal similarities and differences in resources and potentials of individual-professional development of university students; on this basis, to develop the contours of the corresponding empirical model.Methodology and research methods. The work is based on a system-integrative approach to the study of individuality. Initially, this approach involves the identification (differentiation) of the basic components of the system followed by the reverse process - their commonality (integration) into the system. The systematisation of the main positions of the formed model was performed in accordance with the problem and comparative analysis based on the inductive method.Results and scientific novelty. Students' resources and potentials are developed through common grounds, linking them to a special class system with a dual configuration. In this system, the phenomena under discussion differ in the way of existence and position on the time axis. Their common feature and integrator is the category of possible, which brings integrity to this system. The formulated hypotheses are aimed at finding independent variables of the designed empirical model - resources and potentials of students' academic achievements. The list of hypotheses includes testing of self-control variables in the form of a separate item as a mediating link. On this basis, a new understanding of student individual-professional development in higher school is presented.An integrative model of such student development was built, in which the time factor is taken into account. It is demonstrated that this development can be based on a spiral type - as cyclic continuous transitions from resources to potentials with subsequent transformations of the latter into resources again, but with updated possibilities. In spiral transitions, amalgam formation from different-quality components occurs and mediating links of the system appear. The role of cognitive resources and potentials in academic achievements and learning activities is identified. The relevance of elements of the proposed model to solved educational tasks is a key question for successful implementation of such learning activity.Practical significance. The research materials enrich the understanding of the content of the concepts of "resource", "potential" and their contribution to the academic achievements of students. The obtained results contribute to the spread of a systemic approach in the field of research practice for the study of resources and potentials, overcoming lack of integration and creation of integrative models. The described research strategy can be used in teaching the disciplines of "Personality Psychology", "Cognitive Psychology" and "Developmental Psychology" in classical and pedagogical universities.